Allelic variants of a potato HEAT SHOCK COGNATE 70 gene confer improved tuber yield under a wide range of environmental conditions - Campbell, R.; Ducreux, L.; Cowan, G.; Young, V.; Chinoko, G.; Chitedze, G.; Kwendani, S.; Chiipanthenga, M.; Bita, C.E.; Mwenye, O.; Were, H.; Torrance, L.; et al. (Wiley, 2023)
Previously, we developed and applied a glasshouse screen for potato tuber yield under heat stress and identified a candidate gene (HSc70) for heat tolerance by genetic analysis of a diploid potato population. Specific allelic variants were expressed at high levels on exposure to moderately elevated temperature due to variations in gene promoter sequence. In this study, we aimed to confirm the results from the glasshouse screen in field trials conducted over several seasons and locations including those in Kenya, Malawi and the UK. We extend our understanding of the HSc70 gene and demonstrate that expression level of HSc70 correlates with tolerance to heat stress in a wide range of wild potato relatives. The physiological basis of the protective effect of HSc70 was explored and we show that genotypes carrying the highly expressed HSc70 A2 allele are protected against photooxidative damage to PSII induced by abiotic stresses. Overall, we show the potential of HSc70 alleles for breeding resilient potato genotypes for multiple environments.